PENGARUH UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN DEWAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Dir, Karolina Yunita; Halim, Abdul; Mustikowati, Rita Indah (Jurnal Riset Mahasiswa Akuntansi, 2019)
This study aims to explain and test how the influence of company size and capital structure on firm value with an independent board of commissioners as a moderating variable in banking companies listed on the Indonesia Stock Exchange in the period 2016-2017. This type of research is explanatory research, namely by using classical assumptions, using moderated regression analysis, and using the t test. The number of samples is 39 companies, and the sampling method is using purposive judgment sampling. The variables in this study consisted of company size and capital structure as an independent variable, company value as the dependent variable and the independent board of commissioners as moderation. The result of the analysis is that partially the size of the company affects the value of the company, the capital structure influences the value of the company, the independent board of commissioners strengthens the influence of the size of the company on the value of the company and the independent board of commissioners strengthens the effect of the capital structure on the value of the company.